Metabolomics Analysis Across Multiple Biofluids Reveals the Metabolic Responses of Lactating Holstein Dairy Cows to Fermented Soybean Meal Replacement - Wang, Zuo; Yu, Yuannian; Shen, Weijun; Tan, Zhiliang; Tang, Shaoxun; Yao, Hui; He, Jianhua; Wan, Fachun (Frontiers in Veterinary Science, 2022)
This experiment was performed to reveal the metabolic responses of dairy cows to the replacement of soybean meal (SBM) by fermented soybean meal (FSBM). Twenty-four lactating Chinese Holstein dairy cattle were assigned to either the SBM group [the basal total mixed ration (TMR) diet containing 5.77% SBM] or the FSBM group (the experimental TMR diet containing 5.55% FSBM), in a completely randomized design. The entire period of this trial consisted of 14 days for adjustment and 40 days for data and sample collection, and sampling for rumen liquid, blood, milk, and urine were conducted on 34 d and 54 d, respectively. When SBM was completely replaced by FSBM, the levels of several medium-chain FA in milk (i.e., C13:0, C14:1, and C16:0) rose significantly (P < 0.05), while the concentrations of a few milk long-chain FA (i.e., C17:0, C18:0, C18:1n9c, and C20:0) declined significantly (P < 0.05). Besides, the densities of urea nitrogen and lactic acid were significantly (P < 0.05) higher, while the glucose concentration was significantly (P < 0.05) lower in the blood of the FSBM-fed cows than the SBM-fed cows. Based on the metabolomics analysis simultaneously targeting the rumen liquid, plasma, milk, and urine, it was noticed that substituting FSBM for SBM altered the metabolic profiles of all the four biofluids. According to the identified significantly different metabolites, 3 and 2 amino acid-relevant metabolic pathways were identified as the significantly different pathways between the two treatments in the rumen fluid and urine, respectively. Furthermore, the glycine, serine and threonine metabolism, valine, leucine and isoleucine biosynthesis, and cysteine and methionine metabolism were the three key integrated different pathways identified in this study. Results mainly implied that the FSBM replacement could enhance the nitrogen utilization and possibly influence the inflammatory reactions and antioxidative functions of dairy cattle. The differential metabolites and relevant pathways discovered in this experiment could serve as biomarkers for the alterations in protein feed and nitrogen utilization efficiency of dairy cows, and further investigations are needed to elucidate the definite roles and correlations of the differential metabolites and pathways.